Stroke–a medical emergency. Issue 1 (1st January 1999) - Lott, C; Hennes, H J; Dick, W
Abstract : Stroke is the third leading cause of death and number one cause of disability in industrialised countries. A number of new therapeutic approaches are currently in development for use in the acute phase of ischaemic stroke and all trials have, to date, demonstrated the importance of early diagnosis and subsequent initiation of treatment. It is well known that, for most patients, there is a long delay between the onset of symptoms and the start of treatment. A number of factors are responsible for this time delay: signs and symptoms often go unrecognised by patients, relatives, and bystanders and, unlike trauma or myocardial infarction, stroke is not given a high priority by medical staff. Studies into the pathophysiology of acute ischaemic stroke have indicated that treatment options are likely to be optimised when early signs of stroke are recognised and treatment is initiated within six hours of symptom onset. Although a small number of stroke patients are treated as emergencies and attended to by the emergency medical services within this time window, this number could easily be increased by intensified public and emergency personnel education. In the future, it is hoped that treatments which must be administered within the first few hours of acute stroke will be able to be initiated by the emergency medical services. In the same way that hospitals are notified and prepared in advance to receive trauma victims, early notification by the emergency medical services about stroke patients would enable stroke teams to be present at admission, thus improving the likelihood of a better outcome for patients.